Regional disaster risk management strategies for food security: Probing Southern African Development Community channels for influencing national policy - Tirivangasi, Happy M. (Jàmbá - Journal of Disaster Risk Studies, 2018)
Natural disasters and food insecurity are directly interconnected. Climate change related hazards such as floods, hurricanes, tsunamis, droughts and other risks can weaken food security and severely impact agricultural activities. Consequently, this has an impact on market access, trade, food supply, reduced income, increased food prices, decreased farm income and employment. Natural disasters create poverty, which in turn increases the prevalence of food insecurity and malnutrition. It is clear that disasters put food security at risk. The poorest people in the community are affected by food insecurity and disasters; hence, there is a need to be prepared as well as be in a position to manage disasters. Without serious efforts to address them, the risks of disasters will become an increasingly serious obstacle to sustainable development and the achievement of sustainable development goals, particularly goal number 2 ‘end hunger, achieve food security and improved nutrition and promote sustainable agriculture’. In recent years, countries in southern Africa have experienced an increase in the frequency, magnitude and impact of climate change–related hazards such as droughts, veld fire, depleting water resources and flood events. This research aims to reveal Southern African Development Community disaster risk management strategies for food security to see how they an influence and shape policy at the national level in southern Africa. Sustainable Livelihood approach was adopted as the main theoretical framework for the study. The qualitative Analysis is based largely on data from databases such as national reports, regional reports and empirical findings on the disaster management–sustainable development nexus.
Article published in the Jàmbá:Journal of Disaster Risk Studies; vol 10(1), a468. https://doi.org/10.4102/jamba.v10i1.468
Keywords: Regional disaster risk management strategies; Food security; Southern African Development Community; National policy; Food security-Climatic factors